2023
DOI: 10.1186/s13063-023-07277-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of the COVID-19 pandemic on clinical trial screening rates over time in 37 countries

Abstract: The COVID-19 pandemic has had an unprecedented and disruptive impact on people’s health and lives worldwide. In addition to burdening people’s health in the short-term in the form of infection, illness, and mortality, there has been an enormous negative impact on clinical research. Clinical trials experienced challenges in ensuring patient safety and enrolling new patients throughout the pandemic. Here, we investigate and quantify the negative impact that the COVID-19 pandemic has industry-sponsored clinical t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In addition, the operating theatre availability was substantially decreased for non-life-threatening conditions or non-urgent surgical procedures. These findings are in accordance with the literature on the impact of COVID-19 on clinical trial screening rates [ 28 ], indicating that there is a negative correlation between the severity of the global pandemic and the number of screenings in clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the operating theatre availability was substantially decreased for non-life-threatening conditions or non-urgent surgical procedures. These findings are in accordance with the literature on the impact of COVID-19 on clinical trial screening rates [ 28 ], indicating that there is a negative correlation between the severity of the global pandemic and the number of screenings in clinical trials.…”
Section: Discussionsupporting
confidence: 92%
“…Another study of 321 218 non‐COVID‐19 clinical trials found that among trials stopped from January 2017 to May 2020, an average of 1147 trials per month were stopped during the start of the pandemic (the first 5 months of 2020), compared with 638 trials per month from 2017 to 2019 [ 7 ]. A more recent analysis sought to quantify the impact of the pandemic on industry‐sponsored clinical trials, demonstrating that year‐over‐year clinical trial screening rates declined sharply from 2019 to 2020, with a slight rebound in 2021 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…We initially planned to enroll 100 patients into this study based on power calculations of possible differences between groups in cognition and function after 20 weeks. However, due to challenges in recruiting patients, especially with the COVID-19 emergency and that many pharma trials began recruiting patients with similar criteria, it took longer to enroll patients than initially planned [21]. Because of this, we terminated recruitment after 51 patients were enrolled.…”
Section: Participants and Methodsmentioning
confidence: 99%